2018
DOI: 10.1016/j.jep.2017.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterization and cytotoxic, genotoxic, and mutagenic properties of Baccharis trinervis (Lam, Persoon) from Colombia and Brazil

Abstract: Cytotoxic and genotoxic effects were demonstrated in all extracts and fractions used, although only EAF showed mutagenic effects by CBMN, but not by Salmonella/microsome assay. Our results suggest that flavonoids, phenylpropanoids, coumarins, and diterpenes may be responsible for the cytotoxic, genotoxic and mutagenic effects observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…The risk-benefit ratio of any drug substance is an influential criterion for the recommendation as a therapy in human diseases (Jaramillo-García et al, 2018). In the present study, methanolic extract of (Capello, Fischer, & Hungerbühler, 2007).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The risk-benefit ratio of any drug substance is an influential criterion for the recommendation as a therapy in human diseases (Jaramillo-García et al, 2018). In the present study, methanolic extract of (Capello, Fischer, & Hungerbühler, 2007).…”
Section: Discussionmentioning
confidence: 89%
“…The results of cytotoxicity assay are in concordance to the results of other species of this genus such as M. oleifera leaf callus, and stem bark extracts on HeLa cell line(Jafarain, Asghari, & Ghassami, 2014;Kumbhare, Guleha, & Sivakumar, 2012;Nair & Varalakshmi, 2011). The cytotoxic potential of the plant might be due to its phenols, flavonoids, alkaloids as reported earlier(Jaramillo-García et al, 2018;Özçelik, Kartal, & Orhan, 2011;…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Antimicrobial and antiviral: several in vitro studies showed moderate activity of aqueous extracts of the aerial parts and the essential oil against pathogenic bacteria and fungi as well as against Herpes simplex and HI Virus strains, as reviewed (Jaramillo-Garcıá et al, 2018).…”
Section: Safe and Effective D31mentioning
confidence: 99%
“…Cytotoxic and genotoxic effects of aqueous extract of the aerial parts and different organic solvent fractions were reported in different assays (Jaramillo-Garcıá et al, 2018). Antidiabetic: a number of in vitro and in vivo studies reported significant effects (incl.…”
Section: Safe and Effective D31mentioning
confidence: 99%